Securitization of Local Maritime Governance: The Institutional Role of Poskamladu Tamperan in the Maritime Security System of Pacitan Bay - Chalid Darmawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Maritime security has evolved beyond traditional military concerns to encompass multidimensional non-traditional threats, particularly at the local governance level. This study analyzes the securitization process of the Integrated Maritime Security Post (Poskamladu) at Tamperan Port within the maritime security system of Pacitan Bay. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. The analysis applies the Copenhagen School’s securitization framework, focusing on securitizing actors, existential threats, speech acts, and referent objects. The findings indicate that Poskamladu functions as a securitizing actor by framing non-traditional issues—illegal fishing, coastal spatial conflicts, and disorderly port activities—as existential threats to marine sustainability, community stability, and local economic security. Unlike classical securitization models emphasizing formal declarations, securitization at Tamperan occurs through informal, practice-based speech acts embedded in mediation, coordination, and licensing control. However, the effectiveness of this securitization process is constrained by fragmented authority, limited infrastructure capacity, and insufficient preparedness for technology-based threats. This study contributes theoretically by extending securitization analysis to subnational maritime governance and highlighting the role of informal institutional practices in constructing security threats.